2020
DOI: 10.1177/0300060520902606
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the Ambu® AuraOnce™ laryngeal mask and endotracheal intubation in anesthesia airway management during neurosurgery

Abstract: Objective: To investigate the feasibility and efficacy of the Ambu V R AuraOnce TM laryngeal mask (LMA) compared with endotracheal intubation (ETI) during supratentorial tumor resection in the right lateral decubitus position. Methods: This was a randomized controlled trial of LMA compared with ETI in patients who were scheduled to undergo supratentorial tumor resection in the right lateral decubitus position. The patients were randomized to the LMA (n ¼ 40) and ETI groups (n ¼ 40). The hemodynamic parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Stimuli can lead to hypertension, tachycardia, and catecholamine release. [ 13 14 ] It may be harmful to patients with hypertension, glaucoma, cardiovascular disease, and cerebrovascular malformations. In our study, the differences in drugs used to raise blood pressure, lower blood pressure, increase heart rate, and reduce heart rate during surgery between the two groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli can lead to hypertension, tachycardia, and catecholamine release. [ 13 14 ] It may be harmful to patients with hypertension, glaucoma, cardiovascular disease, and cerebrovascular malformations. In our study, the differences in drugs used to raise blood pressure, lower blood pressure, increase heart rate, and reduce heart rate during surgery between the two groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The double lumen LMA is used in various operations because it greatly reduces reflux and aspiration [ 16 ]. Previous study showed that anesthesia using LMA (Laryngeal Mask Airway) during general anesthesia reduced hemodynamic fluctuation during surgery compared to endotracheal intubation [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia with tracheal intubation requires deeper anesthesia and proper muscle relaxation during the induction as well as maintenance of anesthesia. During tracheal intubation and extubation, there are often substantial hemodynamic uctuations that are extremely harmful to patients with aneurysms; these often cause serious adverse reactions such as cerebral aneurysm rupture and hemorrhage [22,23].…”
Section: Discussionmentioning
confidence: 99%